Risk factors associated with dyspepsia in a rural Asian population and its impact on quality of life - Mahadeva, S.; Yadav, H.; Rampal, S.; Goh, Khean-Lee (Elsevier, 2010)
OBJECTIVES: The epidemiology and impact of dyspepsia in rural Asia remains uncertain. We aimed to determine the prevalence epidemiology and impact of dyspepsia in a rural Malaysian community. METHODS: A door-to-door survey was conducted in a representative rural population in Malaysia. Dyspepsia was defined according to the Rome II criteria, and health-related quality of life (HRQOL) was assessed using the Euroqol (EQ-5D) instrument. RESULTS: Of 2,260 adults, 2,000 (88.5%) completed the survey. The mean age of respondents was 40.4 +/- 15.3 years, 62.7% were women, 79.0% were ethnic Malays, 8.4% had been educated up to the tertiary level, 49.7% were unemployed, and 63.4% resided in village-type housing with 49.1% having > 8 residents per household. Dyspepsia was prevalent in 292 (14.6%) adults, and they had lower mean EQ-5D utility scores compared with healthy controls (0.91 +/- 0.17 vs. 0.97 +/- 0.08, P < 0.0001). Dyspepsia was found to be associated with female gender (15.8 vs. 12.7% males, P = 0.058), Chinese ethnicity (19.7 vs. 14.2% non-Chinese), higher education levels, medium-range incomes (19.1% medium range vs. 13.3% low range), non-village-type housing (16.3 vs. 13.5% village-type house, P = 0.08), nonsmokers (18.7 vs. 13.7%, P = 0.015), non-tea drinkers (19.5 vs. 12.3%, P < 0.0001), regular analgesia intake (27 vs. 12.7%, P < 0.0001), and adults with chronic illness (26.6 vs. 11.1%, P < 0.0001). Logistic regression analysis showed that higher levels of education, i.e., secondary (odds ratio (OR) 2.13, 95% confidence interval (CI) = 1.15-3.93) and tertiary (2.70, 95% CI = 1.30-5.62) education, non-village housing (OR 1.36, 95% CI = 1.02-1.80), regular analgesia (OR 2.22, 95% CI = 1.60-3.09), and chronic illness (OR 2.83, 95% CI = 2.12 -3.77) were independent risk factors for dyspepsia. Conversely, regular tea drinking (OR 0.59) seemed to have an inverse relationship. CONCLUSIONS: Dyspepsia in rural Malaysians is associated with a lower HRQOL. Epidemiological risk factors include a higher socioeconomic status, regular analgesic consumption, and chronic illness.